A Robotics-Based Approach to Modeling of Choice Reaching Experiments on Visual Attention - Strauss, Soeren; Heinke, Dietmar (Frontiers in Psychology, 2012)
The paper presents a robotics-based model for choice reaching experiments on visual attention. In these experiments participants were asked to make rapid reach movements towards a target in an odd-colour search task, i.e. reaching for a green square among red squares and vice versa (e.g. Song & Nakayama, 2008). Interestingly these studies found that in a high number of trials movements were initially directed towards a distractor and only later were adjusted towards the target. These ”curved” trajectories occurred particularly frequently when the target in the directly preceding trial had a different colour (priming effect). Our model is embedded in a closed-loop control of a LEGO robot arm aiming to mimic these reach movements. The model is based on our earlier work which suggests that target selection in visual search is implemented through parallel interactions between competitive and cooperative processes in the brain (Heinke & Backhaus, 2011; Heinke & Humphreys, 2003). To link this model with the control of the robot arm we implemented a topological representation of movement parameters following the dynamic field theory (Erlhagen & Schoener, 2002). The robot arm is able to mimic the results of the odd-colour search task including the priming effect and also generates human-like trajectories with a bell-shaped velocity profile. Theoretical implications and predictions are discussed in the paper.